YOĞUN BAKIMDA TAKİP EDİLEN COVID-19 TANILI HASTALARIN RETROSPEKTİF İNCELENMESİ - AKEL, DERYA SEZEN (Fırat Üniveristesi, 2022)
Coronavirus Disease-19 (COVID-19), Akut Solunum Sıkıntısı Sendromu (ARDS), sepsis, septik şok, miyokardit, aritmi, kardiyojenik şok veya çoklu organ yetmezliği tablolarına sebep olan multisistemik bir hastalıktır. Bu çalışmada yoğun bakımda takip edilen hastaları retrospektif olarak değerlendirilmesi amaçlanmıştır. COVD 19 tanısı ile yoğun bakımda takip edilen 200 hastanın verileri retrospektif olarak incelendi. Yoğun bakım kabulünde temel özellikler, komorbiditeler, yoğun bakım sürecindeki klinik durumlar, solunum desteği tedavileri ve laboratuvar bulguları analiz edildi. Hastaların 124'ü erkek, 76'sı kadındı. 200 hastanın 143'ünde mortalite gerçekleşti. Ölen hastaların yaş ortalaması (70.5 ± 14.02) yaşayanlara göre daha yüksekti (64.3±16.25). Hastaların 154'ünde akciğer tomografisinde COVID 19 ile uyumlu bulgular vardı. Yoğun bakıma yatışta SOFA skoru 5 (0-17), APACHE II skoru 16 (5-37) idi. Hastaların yoğun bakımda yatış süresi 10 (1-64) gün idi. Ölen hastaların yoğun bakıma yatıştaki APACHE II skoru ve SOFA skoru yaşayan hastalardan anlamlı olarak daha yüksekti. ARDS gelişen 180 hastanın 141'inde mortalite gerçekleşti. ARDS gelişmeyen hastalarda mortalite oranı %10'du. Mortalite oranı ARDS gelişen hastalarda anlamlı olarak daha yüksekti. Hastaların yoğun bakıma kabulde laktat değerleri ölen hastalarda ortanca 2,30 (1,80-3,60) iken yaşayan hastalarda 2(1,50-2,50) ve geliş saturasyon değerleri ölen hastalarda 85(82-90) yaşayanlar hastalarda ise 89 (94-92) idi. Ölen hastalarda lenfosit değerinin yoğun bakıma kabuldeki değere göre 14. günde yüzde değişimi %27 azalma şeklinde iken yaşayanlar grubunda %15 artış şeklindeydi. PaO2 /FiO2 oranının 14. Gün yüzde değişimi ölenler grubunda %29 artış yaşayanlar grubunda ise %115 artış şeklindeydi. Yoğun bakıma kabulde LDH değeri ölenler grubunda 630 (37-6517) iken yaşayanlar grubunda 511(216-1434) idi. LDH değerinin 7. gün yüzde değişimi ölenler grubunda %6 artış iken yaşayanlar grubunda %16 azalma şeklindeydi. COVID-19 hastalarında gelişen sepsis, ARDS, MAS, koagülasyon bozukluğu ve böbrek yetmezliği gibi klinik durumların mortalite oranları oldukça yüksektir. Mortalitenin ön görülmesinde yoğun bakıma yatıştaki LDH, SpO2, PaO2 /FiO2 oranı ve laktat değerleri yararlı tetkikler olarak saptanmıştır. Bu hastaların takibinde, lenfosit sayısı, CRP, AST, D-dimer ve ferritin değerleri yararlı olacaktır. Anahtar Kelimeler: COVID-19, Yoğun Bakım Ünitesi, Mortalite

Coronavirus Disease-19 (COVID-19) is a multisystemic disease that causes acute respiratory distress syndrome (ARDS), sepsis, septic shock, myocarditis, arrhythmia, cardiogenic shock or multiple organ failure. In this study, it was aimed to retrospectively evaluate the patients followed in the intensive care unit. The data of 200 patients treated in the intensive care unit with the diagnosis of COVID 19 were analyzed retrospectively. Basic characteristics, comorbidities, clinical conditions during the intensive care unit admission, respiratory support treatments and laboratory findings were analyzed. Of the patients, 124 were male and 76 were female. Mortality occurred in 143 of 200 patients. The mean age of patients who died (70.5 ± 14.02) was higher than those who survived (64.3 ± 16.25). 154 of the patients had findings consistent with COVID 19 in the chest tomography. The SOFA score of the patients was 5 (0-17) and the APACHE II score was 16 (5-37) at the time of admission to the intensive care unit. The median length of stay of the patients in the intensive care unit was 10 (1-64) days. The APACHE II score and SOFA score of the patients who died in the intensive care unit admission were significantly higher than the patients who survived. Mortality occurred in 141 of 180 patients who developed ARDS. The mortality rate in patients who did not develop ARDS was 10%. The mortality rate was significantly higher in patients who developed ARDS. While the median lactate values were 2.30 (1.80-3.60) in the patients who died at admission to the intensive care unit, it was 2 (1.50-2.50) in the patients who survived and 85 (82-90) in the patients who survived, and 89 (82-90) in the patients who died. (94-92). The percent change of lymphocyte value on the 14th day compared to the value at admission to the intensive care unit in the patients who died was a 27% decrease, while it was a 15% increase in the survivors group. The percent change in the PaO2/FiO2 ratio on the 14th day was 29% increase in the deceased group and 115% increase in the survivors group. While the LDH value at admission to the intensive care unit was 630 (37-6517) in the deceased group, it was 511 (216-1434) in the survivors group. The 7th day percent change in LDH value was 6% increase in the deceased group and 16% decrease in the survivor group. The mortality rates of clinical conditions such as sepsis, ARDS, MAS, coagulation disorder and kidney failure in COVID-19 patients are quite high. LDH, SpO2, PaO2/FiO2 ratio and lactate values were found to be useful tests in the prediction of mortality. In the follow-up of these patients, lymphocyte count, CRP, AST, D-dimer and ferritin values will be useful. Keywords: COVID-19, Intensive Care Unit, Mortality
Retrospective examination of patients diagnosed with COVID-19 treated in icu
Keywords: Anestezi ve Reanimasyon